Re-conceptualizing free will for the 21st century: acting independently with a limited role for consciousness - Bonn, Gregory B. (Frontiers in Psychology, 2013)
This paper examines the concept of free will, or independent action, in light of recent research in psychology and neuroscience. Reviewing findings in memory, prospection, and mental simulation, as well as the neurological mechanisms underlying behavioral control, planning, and integration, it is suggested in accord with previous arguments (e.g. Harris, 2012; Wegner, 2003) that a folk conception of free will as entirely conscious control over behavior should be rejected. However, it is argued that, when taken together, these findings can also support an alternative conception of free will. The constructive nature of memory and an integrative “default network” provide the means for novel and creative combinations of information, such as the imagining of counterfactual scenarios and alternative courses of action. Considering recent findings of extensive functional connections between these systems and those that subsume motor control and goal maintenance, it is argued that individuals have the capability of producing novel ideas and translating them into actionable goals. Although most of these processes take place beneath conscious awareness, it is argued that they are unique to the individual and thus can be considered a form of independent control over behavior, or free will.